Henry V [videorecording (DVD)] - Olivier, Laurence, 1907-1989; Newton, Robert, 1905-1956; Banks, Leslie, 1890-1952; Shakespeare, William, 1564-1616 (Criterion collection, 1999)
Historical epic of the English king who defeated the French at Agincourt.